The production performance of Holstein Friesian dairy cattle in West Java - P Mahyudin; S.B Siregar; N Hidayati; T Sugiarti (Jurnal Ilmu Ternak dan Veteriner, 1997)
The production performance of Holstein-Friesian cows in West Java was evaluated in two areas, Cisarua district (Bogor) and Tanjungsari district (Sumedang). In Cisarua the evaluation was made on 175 cows with different stage of lactation (2 - 11 months). Feed offered, both forage and concentrate, milk production and chess girth were measured from each animal for 24 h only. Date of calving, date of service and stage of pregnancy were recorded by interviewing the farmers . In Tanjungsari the study was conducted on 102 postpartum cows . Milk production and chess girth were measured at the beginning of the study and then once a month (morning and afternoon milking) for 3 months. Milk production was 3,700 1 and 3,400 1 per lactation with declining rate of 0 .03 and 0 .05 1/d for Cisarua and Tanjungsari area respectively. The ratio of concentrate : forage consumption was 1 and 1 .4 in Cisarua and in Tanjungsari respectively, and the ratio was reduced as milk production declined . The efficiency of conversion of feed ME to milk yield was approximately the same (0.12 1/MJ) in both location . The proportion of cows lost weight in Cisarua during the first three months was lower (46 %) as compared to that in Sumedang (77 %). Approximately 68 % of the population have conception rate (CR) > 50 % , the remaining should be culled, 24 % have low CR and 8 % have days open > 150 days . From 61 cows observed, 71 % and 21% have a projected calving interval of 12 months and 13 - 14 months respectively . It can be concluded that milk production and reproduction efficiency of Holstein'cows in West Java are considered low.   Key words: Holstein-Friesian cow, reproduction efficiency, milk production